Reproductive homing and fine‐scaled genetic structuring of anadromous Baltic Sea perch (Perca fluviatilis). (28th March 2022) - Hall, Marcus; Koch‐Schmidt, Per; Larsson, Per; Tibblin, Petter; Yıldırım, Yeşerin; Sunde, Johanna
Abstract: To investigate the population dynamics of anadromous Baltic Sea perch Perca fluviatilis (Linnaeus), we studied the migratory behaviour (arrival to spawning location) and population structure (genetic structure and differentiation) of three closely located (<50 km) populations. Spawning migration lasted for 32–80 days, and passive integrated transponder tag (PIT‐tag) data indicated that anadromous perch displayed reproductive homing. Populations were differentiated, despite low levels of gene flow (3%–5%), and differentiation increased with increasing geographic distance. This fine‐scaled spatial structuring was likely, at least partly, explained by homing behaviour. Analyses of temporal within‐stream substructuring yielded inconclusive results, so further studies are required to evaluate this. Taken together, our findings highlight the potential for fine‐scaled genetic structuring in anadromous perch and indicate that multiple mechanisms, such as isolation by distance, homing, and reproductive timing could contribute to this pattern. This illustrates the importance of considering cryptic barriers to accurately identify reproductive units, and points to the need for local management of anadromous perch.